Clostridium difficile infection in hospitalized octogenarian patients. Issue 2 (15th November 2017) - Trifan, Anca; Girleanu, Irina; Stanciu, Carol; Miftode, Egidia; Cojocariu, Camelia; Singeap, Ana‐Maria; Sfarti, Catalin; Chiriac, Stefan; Cuciureanu, Tudor; Stoica, Oana
Abstract : Aim: To evaluate the risk factors and outcome of Clostridium difficile infection in hospitalized octogenarian patients. Methods: A retrospective analysis of risk factors and outcome of C. difficile infection in hospitalized octogenarians was carried out at two academic centers in Romania from January 2014 to September 2016. Demographic, clinical and laboratory characteristics; antibiotics and proton pump inhibitors use in‐hospital and 2 months before admission; comorbidities; length of hospital stay; treatment; and outcome were carefully collected from the patients' medical charts and compared with those from octogenarians hospitalized during the same period. Results: A total of 286 octogenarians were hospitalized during the study period and among them 79 (27.6%) were diagnosed with C. difficile infection. On multivariate logistic regression analyses, the previous 2 months' hospitalizations (OR 10.231, 95% CI 1.769–58.965, P = 0.009), antibiotic use 2 months before admission (OR 12.596, 95% CI 1.024–15.494, P = 0.048), antibiotic treatment during hospitalization (OR 6.302, 95% CI 3.510–11.316, P < 0.0001), arterial hypertension (OR 11.228, 95% CI 1.917–65.783, P = 0.007), chronic kidney disease (OR 4.474, 95% CI 1.037–19.299, P = 0.045) and chronic cardiac failure (OR 7.328, 95% CI 2.068–25.967, P = 0.002) were independently associated with infection. Patients with infection had longer length of hospital stay than those without (15.3 ± 5.1 vs 11.1 ± 4.3 days, P < 0.0001). None of the patients with infection had severe disease, none required surgery and none died during hospitalization. Conclusions: Hospitalized octogenarians with comorbidities, recently hospitalized or receiving antibiotic treatment are at risk for C. difficile infection. Clinicians evaluating such patients should have a high index of suspicion for this infection.Geriatr Gerontol Int 2018; 18: 315–320 .